2019
DOI: 10.24815/jdab.v6i2.13785
|View full text |Cite
|
Sign up to set email alerts
|

Does Eco-Efficiency Improve Financial Performance of Manufacturing Companies in Indonesia?

Abstract: This study aims to determine the impact of environmental performance proxied by eco-efficiency on the financial performance of manufacturing companies in Indonesia. İn this study, the multiple linear regression test was used to analyse the data.  The sample of this study is manufacturing companies that listed at the Indonesia Stock Exchange from 2012 until 2016 with the total observation is 80 firm-years.The results of this study indicated that the average level of eco-efficiency of the manufacturing companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 27 publications
(38 reference statements)
4
19
0
1
Order By: Relevance
“…This means that increased efficiency in the field of ecology is effective for improving the firm's financial performance.This shows that H4 which states that the ecoefficiency variable is associated to firm's financial performance is supported.This is in line with the results of research conducted byMeutia et al (2019). Meanwhile, the result for good corporate governance variable shows that there is no relationship between good…”
supporting
confidence: 89%
See 3 more Smart Citations
“…This means that increased efficiency in the field of ecology is effective for improving the firm's financial performance.This shows that H4 which states that the ecoefficiency variable is associated to firm's financial performance is supported.This is in line with the results of research conducted byMeutia et al (2019). Meanwhile, the result for good corporate governance variable shows that there is no relationship between good…”
supporting
confidence: 89%
“…This means that companies that adopt the eco-efficiency concept have a higher firm value and are able to generate profits in the future than companies that do not adopt the eco-efficiency concept. Research conducted by Meutia et al (2019) also found that eco-efficiency has a positive and significant impact on the firm's financial performance. Based on the description above, the hypotheses that can be used are:…”
Section: Eco-efficiency and Firm Valuementioning
confidence: 91%
See 2 more Smart Citations
“…Selain itu, eco-efficiency dapat diterapkan sebagai sistem manajemen lingkungan untuk mengelola sumberdaya yang dimiliki (Panggau & Septiani, 2017). Eco-efficiency adalah singkatan dari "ecological economic efficiency" sebuah konstruksi yang menunjukkan peningkatan produktivitas dan secara bersamaan mengurangi biaya dengan peningkatan kinerja lingkungan (Meutia et al, 2019).…”
Section: Pendahuluanunclassified